Annual Plan 1995-96 Volume-VIII Hill Areas Government of Assam - Planning Commission (Planning Commission, 1995)
The outlay for 1994-95 for T and T works in the Hill Areas of Assam is Rs. 70.00 lakhs. The Expenditure incurred till Dec. 94 is Rs. 19.60 lakhs spent mostly in establishment and clearance past liabilities.
Government of Assam, Development Commissioner for Hill Areas
Government of Assam, Development Commissioner for Hill Areas